2022
DOI: 10.3390/pr10010105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wind Energy Resources in Jordan Using Different Optimization Techniques

Abstract: Wind energy has become one of the world’s most renewable energy sources in recent years. It is regarded as a clean energy source because it produces no greenhouse gas emissions. The assessment of wind energy resources is an important step in the development of any wind energy conversion system (WECS). As a result, this article examines the wind energy potential of nine Jordanian wind locations: Queen Alia Airport, Civil Amman Airport, King Hussein Airport, Irbid, Mafraq, Ma’an, Ghor Al Safi, Safawi, and Irwais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“… PTPGbadbreak=Puniti=1n()Aeftiαi$$\begin{equation}{P}_{{\rm{TPG}}} = {P}_{{\rm{unit}}}\sum_{i = 1}^n {\left( {{A}_{{\rm{eft}}i}{\alpha }_i} \right)} \end{equation}$$ QTPGbadbreak=Puniti=1n()Aeftiαij=18760Pj$$\begin{equation}{Q}_{{\rm{TPG}}} = {P}_{{\rm{unit}}}\sum_{i = 1}^n {\left( {{A}_{{\rm{eft}}i}{\alpha }_i\sum_{j = 1}^{8760} {{P}_j} } \right)} \end{equation}$$where α i is the slope influencing coefficient of the selected grid i , n is the total grids number in the assessment area, P j is the normalized power generation of a typical wind turbine at the hour j . In some of the existing research, the control strategy of the WTG is considered at the equipment level [46–48]. In this model, those relations are gathered into the ratio α .…”
Section: Assessment Methods and Modelmentioning
confidence: 99%
“… PTPGbadbreak=Puniti=1n()Aeftiαi$$\begin{equation}{P}_{{\rm{TPG}}} = {P}_{{\rm{unit}}}\sum_{i = 1}^n {\left( {{A}_{{\rm{eft}}i}{\alpha }_i} \right)} \end{equation}$$ QTPGbadbreak=Puniti=1n()Aeftiαij=18760Pj$$\begin{equation}{Q}_{{\rm{TPG}}} = {P}_{{\rm{unit}}}\sum_{i = 1}^n {\left( {{A}_{{\rm{eft}}i}{\alpha }_i\sum_{j = 1}^{8760} {{P}_j} } \right)} \end{equation}$$where α i is the slope influencing coefficient of the selected grid i , n is the total grids number in the assessment area, P j is the normalized power generation of a typical wind turbine at the hour j . In some of the existing research, the control strategy of the WTG is considered at the equipment level [46–48]. In this model, those relations are gathered into the ratio α .…”
Section: Assessment Methods and Modelmentioning
confidence: 99%
“…where G and D are ground and diffuse solar radiation in kWh/m 2 , respectively. The symbol ρ refers to the ground reflection, and the radiation coefficients R P , R D , and R R are given by [35][36][37][38][39]:…”
Section: Estimating Of Energy Productionmentioning
confidence: 99%
“…According to the study conducted by Serban et al, [23] Romania's wind potential falls into the category of "good". In a different investigation, wind speed power density and frequency distribution were computed using the Weibull distribution in nine different locations in Jordan [24]. Results showed that Irbid has the lowest wind power density, followed by Ghor Al Safi, and King Hussein Airport has the highest, followed by Queen Alia Airport.…”
Section: Introductionmentioning
confidence: 99%